TRANSLANGUAGING PRACTICES IN WRITTEN PEER FEEDBACK: A CASE STUDY IN A SECOND LANGUAGE WRITING CLASS IN INDONESIA - Candrika Citra Sari; Agita Risma Nurhikmawati (TEFLIN Journal, 2025)
This study aims to examine the use of translanguaging in peer feedback among Indonesian EFL learners and their perceptions of it, addressing a research gap in a naturally multilingual context. This study is based on qualitative data, comprising written peer-feedback and a transcription of a Focus Group Discussion (FGD) discussing views and attitudes related to translanguaging in peer-feedback. The data were collected from thirty university students of an English Paragraph Writing class, all of whom spoke Javanese or Indonesian as their first language (L1). The results reveal that translanguaging occurred most frequently in commentary feedback, relating to both content and form. It facilitated negotiation of meaning by lowering affective filters. Students viewed this practice positively, as it scaffolded their understanding of writing components. The findings suggest the potential for translanguaging to enhance L2 writing instruction. Further research could explore syllabus designs that integrate translanguaging and cultural knowledge within learning activities and examine whether translanguaging can enhance the writing quality of multilingual learners.